Exploring common genetic contributors to neuroprotection from amyloid pathology. Issue 2 (17th March 2022) - Seto, Mabel; Mahoney, Emily R.; Dumitrescu, Logan; Ramanan, Vijay K.; Engelman, Corinne D.; Deming, Yuetiva; Albert, Marilyn; Johnson, Sterling C.; Zetterberg, Henrik; Blennow, Kaj; Vemuri, Prashanthi; Jefferson, Angela L.; et al.
Abstract: Preclinical Alzheimer's disease describes some individuals who harbour Alzheimer's pathologies but are asymptomatic. For this study, we hypothesized that genetic variation may help protect some individuals from Alzheimer's-related neurodegeneration. We therefore conducted a genome-wide association study using 5 891 064 common variants to assess whether genetic variation modifies the association between baseline beta-amyloid, as measured by both cerebrospinal fluid and positron emission tomography, and neurodegeneration defined using MRI measures of hippocampal volume. We combined and jointly analysed genotype, biomarker and neuroimaging data from non-Hispanic white individuals who were enrolled in four longitudinal ageing studies ( n = 1065). Using regression models, we examined the interaction between common genetic variants (Minor Allele Frequency >0.01), including APOE -ɛ4 and APOE -ɛ2, and baseline cerebrospinal levels of amyloid (CSF Aβ42) on baseline hippocampal volume and the longitudinal rate of hippocampal atrophy. For targeted replication of top findings, we analysed an independent dataset ( n = 808) where amyloid burden was assessed by Pittsburgh Compound B ([ 11 C]-PiB) positron emission tomography. In this study, we found that APOE -ɛ4 modified the association between baseline CSF Aβ42 and hippocampal volume such that APOE -ɛ4 carriers showed more rapid atrophy, particularly in the presence of enhanced amyloidosis. We also identified a novel locus on chromosome 3 that interacted with baseline CSF Aβ42. Minor allele carriers of rs62263260, an expression quantitative trait locus for the SEMA5B gene ( P = 1.46 × 10 −8 ; 3:122675327) had more rapid neurodegeneration when amyloid burden was high and slower neurodegeneration when amyloid was low. The rs62263260 × amyloid interaction on longitudinal change in hippocampal volume was replicated in an independent dataset ( P = 0.0112) where amyloid burden was assessed by positron emission tomography. In addition to supporting the established interaction between APOE and amyloid on neurodegeneration, our study identifies a novel locus that modifies the association between beta-amyloid and hippocampal atrophy. Annotation results may implicate SEMA5B, a gene involved in synaptic pruning and axonal guidance, as a high-quality candidate for functional confirmation and future mechanistic analysis. Abstract : Seto et al ., report a novel locus on chromosome 3 that modulates the association between baseline amyloid levels and neurodegeneration. Minor allele carriers of rs62263260 exhibit faster hippocampal atrophy among high brain amyloid burden. Functional annotation links rs62263260 to the SEMA5B gene, which is involved in axonal guidance and neurodevelopment. Graphical Abstract: Graphical Abstract